High mobility group protein B1: a new biomarker of obesity in pregnant women?. (30th October 2014) - Giacobbe, A.; Grasso, R.; Imbesi, G.; Salpietro, C. D.; Grasso, L.; Laganà, A. S.; Triolo, O.; Di Benedetto, A.
Abstract: Obesity is associated with an increased risk of an adverse pregnancy outcome. The aim of this study was to analyze the serum levels of high mobility group protein B1 (HMGB1) in obese pregnant women, to assess the role of this protein in the pathogenesis of this disease and to evaluate its possible function as a diagnostic marker for obesity-related complications in obese women. Study participants were randomly selected, from a cohort of pregnant women afferent to our department. A total of 120 women were enrolled in this study: 60 pregnant women had normal body mass index (BMI) and 60 women resulted obese. Pre-pregnancy BMI, weight increase and HMGB1 levels were evaluated for each pregnant woman enrolled. Matching serum HMGB1 levels in two groups, our data evidenced higher levels in the obese women, with a statistically significant difference ( p = 0.0023). A significant positive univariate correlation was observed between serum HMGB1 levels and BMI in obese women. HMGB1 serum levels may therefore represent a predictive marker of disease in pregnant women ( r = 20.9 and p = 0.0001). Further studies are needed in order to validate the role of this cytokine, with the aim of making it possible to use in clinical practice not only for diagnostic purposes, but especially for the early recognition of complications related to it. Chinese abstract: 肥胖与不良妊娠结局风险的升高相关。本研究的目的在于分析妊娠女性血清中高速泳动族蛋白族蛋白B1（HMGB1）水平，评估此蛋白与肥胖发病机制的相关性，判断其作为肥胖女性的肥胖相关并发症诊断标志物的可能性。 本研究受试者从我科室就诊的妊娠女性中随机抽取。研究共纳入120名女性：60名身体质量指数（BMI）正常的妊娠女性，60名肥胖妊娠女性。研究评估了每名受试者妊娠前BMI、体重增加情况及HMGB1水平。研究将血清HMGB1水平匹配为2组，数据表明肥胖组HMGB1水平更高，差异有统计学意义（ p = 0.0023）。肥胖组血清HMGB1水平与BMI之间存在显著单变量相关性。因此，血清HMGB1水平也许可以作为预测妊娠女性相关疾病的指标（ r = 20.9, p = 0.0001）。关于该细胞因子的作用还需进一步研究证实，进而使其在临床上不仅用于诊断肥胖这一疾病，还可用于识别早期相关并发症。